2006
DOI: 10.1002/hep.21340
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effect of adefovir on the number and functionality of myeloid dendritic cells of patients with chronic HBV†

Abstract: In patients with chronic hepatitis B virus (HBV), 2 predominant precursor dendritic cell (DC) subtypes, the myeloid dendritic cell (mDC) and the plasmacytoid dendritic cell (pDC), were recently found to be functionally impaired. HBV DNA was found to be present in the DC subtypes, but no viral replication could be detected. The question remains whether simply the presence of the virus and viral proteins causes this dysfunction of DCs. To address this issue, the effect of viral load reduction resulting from trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…Pediatric patients with immune active disease or infants born to mothers with .5310 7 copies/ml HBV also showed a reduced pDC frequency in the blood. 12,24 In two studies where reduced frequencies were observed in adult patients, the pDC numbers recovered with antiviral therapy, 18,25 again suggesting that DC frequency can be restored with effective treatment.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric patients with immune active disease or infants born to mothers with .5310 7 copies/ml HBV also showed a reduced pDC frequency in the blood. 12,24 In two studies where reduced frequencies were observed in adult patients, the pDC numbers recovered with antiviral therapy, 18,25 again suggesting that DC frequency can be restored with effective treatment.…”
Section: Overviewmentioning
confidence: 99%
“…Zhang et al 12 reported a lower frequency of mDCs in the blood of immune active pediatric patients, but not in those who were immune-tolerant. A study by van der Molen et al 18 found that mDC frequencies were reduced in chronic HBV patients. However, mDC frequency could be returned to the level of healthy donors with antiviral therapy.…”
Section: Overviewmentioning
confidence: 99%
“…Recent studies have demonstrated the functional impairment of mDCs and pDCs in patients with chronic HBV infection. [17][18][19] Notably, these dendritic cells accumulate mostly in the liver of ACLF patients; 7,8,14 however, any correlation between the DCs and corticosteroid efficacy is unknown.…”
Section: 2mentioning
confidence: 99%
“…ADV has a broad-spectrum of antiviral activity, targeting herpesvirus, retroviruses and hepadnaviruses (7,20) and potently inhibits the replication of wild-type HBV and lamivudine-resistant strains (3). In this study, the serum HBV DNA levels in the majority (77.3%, 17/22) of CHB patients were decreased to the levels less than the detection limit following 24 weeks of ADV treatment, although certain patients, e.g., Patient 3, had no or little response to the ADV treatment, which may be associated with ADV resistance (21).…”
Section: Discussionmentioning
confidence: 99%
“…CHB is the result of a complex interaction between a replicating non-cytopathic virus and a down-regulated anti-viral immune response of the patient. Strong humoral and cellular immune responses are required for complete recovery from CHB (3). Therefore, there is an increasing interest in investigating the host immune response to antiviral therapy in order to develop novel therapeutic approaches or to improve clinically available agents.…”
Section: Introductionmentioning
confidence: 99%